Comparison of colistin monotherapy and non-colistin combinations in the treatment of multi-drug resistant Acinetobacter spp. bloodstream infections: A Multicenter retrospective analysis - BEKİROĞLU, GÜLNAZ NURAL (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2015)
Objectives: To compare the efficacy of colistin (COL) monotherapy versus non-COL based combinations in the treatment of bloodstream infections (BSIs) due to multidrug resistant Acinetobacter spp.(MDR-A) . Materials and Methods: Retrospective data of 107 MDR-A BSI cases from 27 tertiary centers in Turkey were included. Primary End-Point: 14-day mortality. Secondary End-Points: Microbial eradication and clinical improvement. Results: Thirty-six patients in the COL monotherapy (CM) group and 71 in the non-COL based combinations (NCC) group were included in the study. Mean age was 59.98 20 years (range: 18-89) and 50.5% were male. Median duration of follow-up was 40 days (range: 9-297). The 14-day survival rates were 52.8% in CM and 47.23% in NCC group (P = 0.36). Microbiological eradication was achieved in 69% of CM and 83% of NCC group (P = 0.13). Treatment failure was detected in 22.9% of cases in both CM and NCC groups. Univariate analysis revealed that mean age (P = 0.001), Charlson comorbidity index (P = 0.03), duration of hospital stay before MDR-A BSI (P = 0.04), Pitt bacteremia score (P = 0.043) and Acute Physiology and Chronic Health Evaluation II score (P = 0.05) were significant in terms of 14-day mortality. Advanced age (P = 0.01) and duration of hospital stay before MDR-A BSI (P = 0.04) were independently associated with 14-day mortality in multivariate analysis. Conclusion: No significant difference was detected between CM and non-COL based combinations in the treatment of MDR-A BSIs in terms of efficacy and 14-day mortality.
Keywords: Blood stream infection; colistin; monotherapy; multi drug resistant Acinetobacter spp; GRAM-NEGATIVE BACTERIA; CRITICALLY-ILL PATIENTS; BAUMANNII BACTEREMIA; RISK-FACTORS; ANTIMICROBIAL THERAPY; MATCHED COHORT; MORTALITY; OUTCOMES; IMPACT; TIGECYCLINE